2016
DOI: 10.1590/s0100-83582016340300017
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the Mechanism of Glyphosate Resistance in Italian Ryegrass Biotypes

Abstract: -The intense use of glyphosate for weed control led to the emergence of several cases of resistance to this herbicide. Weeds can survive the application of herbicides due to several factors, which may or may not be related to the herbicide site of action. The objectives of this study were to quantify the accumulation of shikimate in ryegrass biotypes in response to glyphosate application; investigate possible mutations on the EPSPs gene in susceptible and resistant biotypes; and evaluate the response of ryegra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…So, the aims of this work are firstly to test the in vitro phytotoxic activity (of previously analysed commercial essential oils, winter savory, peppermint, and anise, in order to assure their main compounds by GC/MS) against seed germination and seedling growth of P. oleracea , a cosmopolitan annual weed of tropical and subtropical climates; L. multiflorum , because Lolium spp. has been ranked as one of the specimens most frequently exhibiting herbicide resistance in many countries [30,31,32]; and E. crus-galli , a serious weed of irrigation crops, especially rice. Secondly, we aim to corroborate in vivo the previous in vitro phytotoxic effect using a commercial emulsifiable concentrate with the more phytotoxic essential oils and finally, we will study their potential hazard against maize ( Zea mays L.), rice ( Oryza sativa L.), and tomato ( Solanum lycopersicum L.) seeds in order to obtain selective bioherbicides for food crops.…”
Section: Introductionmentioning
confidence: 99%
“…So, the aims of this work are firstly to test the in vitro phytotoxic activity (of previously analysed commercial essential oils, winter savory, peppermint, and anise, in order to assure their main compounds by GC/MS) against seed germination and seedling growth of P. oleracea , a cosmopolitan annual weed of tropical and subtropical climates; L. multiflorum , because Lolium spp. has been ranked as one of the specimens most frequently exhibiting herbicide resistance in many countries [30,31,32]; and E. crus-galli , a serious weed of irrigation crops, especially rice. Secondly, we aim to corroborate in vivo the previous in vitro phytotoxic effect using a commercial emulsifiable concentrate with the more phytotoxic essential oils and finally, we will study their potential hazard against maize ( Zea mays L.), rice ( Oryza sativa L.), and tomato ( Solanum lycopersicum L.) seeds in order to obtain selective bioherbicides for food crops.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 25 seedlings from five glyphosate-resistant diploid Italian ryegrass plants (SVA04 biotype) harvested in São Valentin-RS, previously characterized with nontarget site resistance (Vargas et al 2016), were transplanted separately in trays containing soil and substrate in a 3:1 proportion. Glyphosate herbicide (Glifosato Atanor 48) at a rate of 2160 g a.e.•ha -1 was applied at the beginning tillering stage to confirm the herbicide-resistance.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Italian ryegrass (Lolium multiflorum Lam.) is a troublesome winter annual grass found in agricultural systems cultivated with wheat and barley, and widely used as forage to animal feed and soil cover plant (Vargas et al 2016). In the last years, the area cultivated with tetraploid Italian ryegrass has been increasing in the Southern Brazilian fields due to the occurrence of diploid glyphosate-resistant populations, and its characteristics such as higher yield of pasture and nutritive value compared to diploid plants (Oliveira et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance mechanism of ryegrass to glyphosate has not yet been fully understood (Vargas et al, 2016). Some studies have suggested a reduction in the absorption and translocation (Ghanizadeh et al, 2016;Fernández-Moreno et al, 2017) and others the overexpression of the EPSPs enzyme (Salas et al, 2015) and the sequestration of the herbicide in the vacuole (Ge et al, 2012).…”
Section: Figure 6 -mentioning
confidence: 99%